KONSEP HEGOUMENOS DALAM IBRANI 13: SEBUAH PROPOSAL UNTUK KEPEMIMPINAN KRISTEN MASA KINI - Karwur, Edwin (STT INDONESIA MANADO, 2020)
The word ‘authority’ is often considered as irrelevant concept or approached suspiciously in the context of Christian leadership. Irrelevant since it is understood as the word that carries a sense of power instead of humility. Suspiciously since it is from time to time, exercised negatively by those in the leadership position. Consequently, leaders are either having difficulties to lead their churches or organizations or failing to achieve the goals of their ministries. The truth is that the Bible teaches about the fact that leaders do have authority and the church, and the people of God ought to respect that. That is the whole nature of this journal. The concept of authority in the Christian leadership context is found in the usage of the word hegoumenos (plural hegoumenoi) particularly in Hebrew 13. This journal will examine extensively the concept of hegoumenos (pemimpin) in Hebrew 13 with a descriptive approach to the whole New Testament regarding that particular concept.